Promoting resilience and emotional well-being of transgender young people: research at the intersections of gender and sexuality. (16th March 2017) - Zeeman, Laetitia; Aranda, Kay; Sherriff, Nigel; Cocking, Chris
ABSTRACT: Within lesbian, gay, bisexual and transgender (LGBT) research there is increasing health-related scholarship on trans lives, with a growing awareness of the impact of health inequalities on trans well-being. The aim of the paper is to provide greater understanding of transgender young people's views of what is needed to promote their emotional well-being and resilience by undertaking specific analysis of data collected as part of wider research with young people ( n  = 97). The study utilised participatory qualitative methods with a cross sectional design generating data via a focus group with trans youth ( n  = 5), followed by thematic analysis. Findings suggest that both individual and collective capacities or resources enable and sustain resilience and well-being for trans young people. The adversity trans youth face is present in school, the community and in healthcare, but they are able to find places where they feel safe and connected to others. Practitioners, teachers and school nurses are well positioned to facilitate structural change in alliance with trans youth to promote resilience. Research results were utilised to inform health improvement, commissioning and service delivery.